2012
DOI: 10.4028/www.scientific.net/amr.463-464.565
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Chemical Evaluation of Wood Plastic Nanocomposite

Abstract: Most applications expose the materials to wide range of temperatures, which may influence on thermal behavior of materials. Thermal degradation of wood polymer composites (WPCs) is a crucial aspect for application and manufacturing process of these products. In this research, wood polymer composites with different nanoclay contents were prepared by melts compounding method. The amount of wood flour and coupling agent were fixed at 40% and 10% wt% (total weight), respectively, and the different levels of nanocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…These exothermic peaks shifted to a higher temperature of Tc = 148.76 °C for nanocomposites with an addition of 3% nanocellulose. This increment was related to the interactions between nanocellulose, polymer chains, and the nucleating agent role of nanocellulose, which increased the crystallization temperature of the Pebax matrix (Chow 2007;Lee et al 2008;Ziaei Tabari et al 2012). The glass transition temperatures of samples are reported in Table 4.…”
Section: Differential Scanning Calorimetry (Dsc) Analysismentioning
confidence: 99%
“…These exothermic peaks shifted to a higher temperature of Tc = 148.76 °C for nanocomposites with an addition of 3% nanocellulose. This increment was related to the interactions between nanocellulose, polymer chains, and the nucleating agent role of nanocellulose, which increased the crystallization temperature of the Pebax matrix (Chow 2007;Lee et al 2008;Ziaei Tabari et al 2012). The glass transition temperatures of samples are reported in Table 4.…”
Section: Differential Scanning Calorimetry (Dsc) Analysismentioning
confidence: 99%
“…For the reduction of formaldehyde emission, Dudkin et al [ 4 ], undertook the addition of aluminum oxide nanoparticles in urea-formaldehyde resin. The use of fibers in composites have many advantages including low cost, high quality, better mechanical properties, environmental friendliness, and reduced energy consumption [ 5 ]. Due to improved thermal, mechanical, and flammability properties, polymer-clay nano-composites have attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization temperature (Tc), enthalpy (ΔHm), and the degree of crystallinity (Xc) of nanocomposites increase with the addition of nanoclay, which indicates that an increasing nanoclay percentage enhances the degradation temperature and thermal stability (Tabari et al 2012). Zahedi et al (2013) reported that walnut shell/polypropylene (PP) composites at the 3.0 wt% organo-clay content had acceptable and comparable properties to wood flour composites.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal degradation of wood plastic composites (WPCs) is a crucial aspect of the application and manufacturing process of WPC products (Tabari et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation